2021
DOI: 10.1038/s41598-021-99210-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of valuable chemicals from glycerol using carbon fiber catalysts derived from ethylene

Abstract: Ethylene was thermocatalytically transformed into carbon products via a CCVD process. The filamentous carbon obtained was further modified with concentrated sulfuric acid or 4‐benzenediazonium sulfonate (BDS) to produce acid-type catalysts. The as-prepared samples were characterized by SEM and TEM techniques to confirm their morphological features. TG, XRD, elemental, and porosity analyses were also performed to assess the quality of these materials. The fabricated carbons were tested in eco-friendly green syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Furthermore, in the DTG curve of CF et , an additional poorly separated signal can be distinguished (at about 750 °C). The above observations can suggest the presence of phases with a different number of defects in CF et , i.e., a slightly more defective phase (with a minimum at 640 °C), and the one more stable and well-organized (with a minimum at 750 °C) 28 , 57 . The absence of lower-temperature peaks excludes contamination of the samples with less thermally stable types of carbon, e.g., amorphous carbon (combustion temp.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Furthermore, in the DTG curve of CF et , an additional poorly separated signal can be distinguished (at about 750 °C). The above observations can suggest the presence of phases with a different number of defects in CF et , i.e., a slightly more defective phase (with a minimum at 640 °C), and the one more stable and well-organized (with a minimum at 750 °C) 28 , 57 . The absence of lower-temperature peaks excludes contamination of the samples with less thermally stable types of carbon, e.g., amorphous carbon (combustion temp.…”
Section: Resultsmentioning
confidence: 79%
“…This indicates that the methods used here for the modifications of CFs were successful. It should be stressed, however, that the degree of sample functionalization was not very high (the S contents between 0.4 and 1.4% were attained), which is not surprising taking into account a rigid and ordered structure of typical carbon fibers 28 , 33 . For comparison, our previous studies showed that modifications of carbon xerogels can produce samples with a 1.4—2.3% S content, while functionalization of carbon polymeric spheres can give materials with a sulfur content of 4.3% 34 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In recent years, carbon materials such as carbon nanotubes and fibers (CNT and CNF, respectively), graphene, carbon dots (CD), hydrothermal carbons (HTC), and activated carbons (AC) have gained increasing attention in the field of catalysis. It has been found that adequately tailored carbons can be used as efficient heterogeneous catalysts for various catalytic processes, including the sustainable transformation of biomass or (bio)glycerol to value-added chemicals [ 19 , 20 , 21 ]. Carbons can also be applied as attractive supports for enzymes, metals, or metal oxide catalysts [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%